2012
DOI: 10.1159/000337904
|View full text |Cite
|
Sign up to set email alerts
|

Physical Activity in Multiple Sclerosis: A Comparative Study of Vitamin D, Brain-Derived Neurotrophic Factor and Regulatory T Cell Populations

Abstract: Background: Previous studies suggest beneficial effects of exercise in multiple sclerosis (MS). However, knowledge on the effects of physical activity on the immune system is limited. Objective: To assess potential relationships between cardiorespiratory fitness, cognitive function, and immune parameters in physically active and inactive MS patients. Methods: We identified 83 patients with relapsing-remitting disease, an unrestricted walking range, and stable interferon-β treatment from our data base. Based on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
6
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 66 publications
2
6
1
Order By: Relevance
“…Similar to the study conducted by Briken et al(2016) who reported the small sample size as one of the reasons why no significant changes were observed in concentration of BDNF after 22 weeks, this study was limited by a the small size of the sample, a fact which can explain why no significant changes were observed in these variables. In the present study, no changes were observed in VDBP level, a finding which is not in line with the results obtained by Waschbisch et al (2012) who reported a positive relationship between fitness level and serum level of vitamin D [40].However, there is no training program in this study and the level of vitamin D is estimated rather than VDBP level, but apparently this is the only study focusing on this variable. Generally, brain is a complex system that may be affected by various environmental factors or drug treatment [31].…”
Section: Discussioncontrasting
confidence: 99%
“…Similar to the study conducted by Briken et al(2016) who reported the small sample size as one of the reasons why no significant changes were observed in concentration of BDNF after 22 weeks, this study was limited by a the small size of the sample, a fact which can explain why no significant changes were observed in these variables. In the present study, no changes were observed in VDBP level, a finding which is not in line with the results obtained by Waschbisch et al (2012) who reported a positive relationship between fitness level and serum level of vitamin D [40].However, there is no training program in this study and the level of vitamin D is estimated rather than VDBP level, but apparently this is the only study focusing on this variable. Generally, brain is a complex system that may be affected by various environmental factors or drug treatment [31].…”
Section: Discussioncontrasting
confidence: 99%
“…We investigated the effect of objectively measured physical activity on 25(OH)D 3 serum levels in pwMS who had EDSS scores � 4 and observed a correlation between daily activity time and 25(OH)D 3 serum levels independent of sun exposure time. This is in line with a previous study, also finding a trend towards higher 25(OH)D 3 serum levels in more active pwMS with an EDSS � 3.5 evaluating the activity status by questionnaire and measurement of cardiorespiratory fitness using spiroergometry, an objective measure of physical performance [10]. The authors assumed that higher vitamin D levels in active people were driven through longer sunlight exposure [10] because the majority of the study population reported longer outdoor rather than indoor activity.…”
Section: Discussionsupporting
confidence: 88%
“…This is in line with a previous study, also finding a trend towards higher 25(OH)D 3 serum levels in more active pwMS with an EDSS � 3.5 evaluating the activity status by questionnaire and measurement of cardiorespiratory fitness using spiroergometry, an objective measure of physical performance [10]. The authors assumed that higher vitamin D levels in active people were driven through longer sunlight exposure [10] because the majority of the study population reported longer outdoor rather than indoor activity. In contrast, we found no association between sunlight exposure time and vitamin D serum levels.…”
Section: Discussionsupporting
confidence: 88%
“…The underlying pathways that activating this relapsing phase are unclear [2,3,8]. Cytokines and their related pathways are considered to be major regulators of the immune system [9,10] which may be important in the evolution of MS lesions and disease activity [9]. During relapse, some important abnormalities and imbalances occur [2,3,8]; therefore, an accurate examination of the effects of environmental stressors such as acute bouts of exercise is essential.…”
Section: Introductionmentioning
confidence: 99%